Protein supplementation augments the skeletal muscle adaptive response to resistance -type exercise training - Cermak, N. M.; Res, P. T.; de Groot, C. P. G. M.; van Loon, L. J. C. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Introduction: Protein ingestion after a single bout of resistance-type exercise stimulates net muscle protein accretion during acute postexercise recovery. Consequently, it is generally believed that protein supplementation is required to maximize the skeletal muscle adaptive response to prolonged resistance-type exercise training. However, there is much discrepancy in the literature on the proposed efficacy of dietary protein supplementation as a means to augment the skeletal muscle adaptive response to resistance-type exercise training. This meta-analysis addresses the issue of whether protein supplementation further augments the increase in muscle mass and strength following prolonged resistance-type exercise training in healthy young and older individuals. Methods: A systematic review of interventional evidence was performed through the use of a random effects meta-analysis model. Data from outcome parameters fat-free mass (FFM), type I and II muscle fiber cross-sectional area (CSA) and muscle strength (1-RM) were collected from randomized controlled trials (RCTs) investigating the impact of dietary protein supplementation during prolonged (>6 wks) resistance-type exercise training. Results: Data from 24 RCTs (746 subjects) were included in May, 2011 and pooled for a random-effects meta-analysis. Protein supplementation demonstrated a positive effect for FFM (weighted mean difference (WMD): 0.75 kg, 95% confidence interval (CI) 0.53, 0.97 kg; P<0.00001) and 1-RM (WMD: 12.4 kg, 95% CI 6.4, 18.3 kg; P<0.0001) compared with a placebo during resistance-type exercise training in both young and older subjects. Protein supplementation further increased type I (WMD: 232 ìm2; 95% CI 128, 336 ìm2; P<0.0001) and type II muscle fiber CSA (417 ìm2; 95% CI 241, 593 ìm2; P<0.00001) following resistance-type exercise training in young subjects. Conclusion: Protein supplementation further improves the gains in fat-free mass and muscle strength during prolonged resistance-type exercise training. As these effects are observed in both young and older subjects, it seems evident that protein supplementation represents an effective nutritional strategy to further improve the benefits of resistance-type exercise training to support healthy aging.